2017
DOI: 10.37358/mp.17.1.4806
|View full text |Cite
|
Sign up to set email alerts
|

Evaluarea liantilor geopolimerici activati alcalin ca alternativa la cimentul Portland

Abstract: This study summarizes the recent achievements in the development of alternative cement free binder materials (cementless) called alkali activated binder or more popularly known as geopolymers. The history of the development of alkali activated binder and recent terminology are discussed. The influence of the type of the base materials on the properties of goepolymers are thoroughly reviewed. The effect of composition and concentration of alkali and curing temperature on the properties and mechanical behavior o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Other researchers detected similar relations and they concluded that alkali concentration can be considered as one of the main parameters in the contribution to the mechanical properties of alkali-activated materials. A high level of calcium compounds can affect the geo-polymerization process and cause deterioration of the samples' microstructure [60,61]. The mortars with mixed activators -NaOH with sodium silicate (N5-S22) and NaOH with CaO (N5-C10) -induced the highest flexural strengths among all combined activated materials.…”
Section: Flexural and Compressive Strengthsmentioning
confidence: 99%
“…Other researchers detected similar relations and they concluded that alkali concentration can be considered as one of the main parameters in the contribution to the mechanical properties of alkali-activated materials. A high level of calcium compounds can affect the geo-polymerization process and cause deterioration of the samples' microstructure [60,61]. The mortars with mixed activators -NaOH with sodium silicate (N5-S22) and NaOH with CaO (N5-C10) -induced the highest flexural strengths among all combined activated materials.…”
Section: Flexural and Compressive Strengthsmentioning
confidence: 99%
“…In this study, fineness size particle (63µm) contains high specific surface area and expected to consume much quantity of water as BA is known to be porous material. Porosity of BA in Portland cement increases and its required high demand of water during cementation process [21,22]. Due to high porosity of BA, results on lower density and higher porosity relative to control mortar will achieved.…”
Section: Densitymentioning
confidence: 99%
“…Numerous studies on alkali-activated concrete have been conducted, but there is still no agreement on the effect of various parameters on the properties of alkali-activated materials. For alkali-activated concrete, the most essential parameters are the aluminosilicate supply, curing conditions, type and concentration of alkaline activator, and alkali activator to base ratio [20][21][22]. NaOH and Na2SiO3 are frequently utilized to activate when making alkali-activated concrete [23].…”
Section: Introductionmentioning
confidence: 99%